Assessment of immunostimulatory responses to the antimiR-22 oligonucleotide compound RES-010 in human peripheral blood mononuclear cells - Panella, Riccardo; Zanderigo, Floriana; Morandini, Francesca; Federico, Denise; Vicentini, Elena; Andreetta, Filippo; Toniolo, Alessandro; Kauppinen, Sakari (Frontiers in Pharmacology, 2023)
microRNA-22 (miR-22) is a key regulator of lipid and energy homeostasis and represents a promising therapeutic target for NAFLD and obesity. We have previously identified a locked nucleic acid (LNA)-modified antisense oligonucleotide compound complementary to miR-22, designated as RES-010 that mediated robust inhibition of miR-22 function in cultured cells and in vivo. In this study we investigated the immune potential of RES-010 in human peripheral blood mononuclear cells (PBMCs). We treated fresh human PBMCs isolated from 6 healthy volunteers with different concentrations of the RES-010 compound and assessed its proinflammatory effects by quantifying IL-1β, IL-6, IFN-γ, TNF-α, IFN-α2a, IFN-β, IL-10 and IL-17A in the supernatants collected 24 hours of treatment with RES-010. The T-cell activation markers, CD69, HLA-DR and CD25 were evaluated by flow cytometry after 24 and 144 hours of treatment, respectively, whereas cell viability was assessed after 24 hours of treatment with RES-010. Our results show that RES-010 compound does not induce any significant immunostimulatory responses in human PBMCs in vitro compared to controls, implying that the proinflammatory potential of RES-010 is low.